Mechanical properties of small structures built by selective laser melting 316 L stainless steel – a phenomenological approach to improve component design. Issue 12 (17th December 2020) - Wiesent, L.; Schultheiß, U.; Lulla, P.; Nonn, A.; Noster, U.
Abstract: Experimental investigations are conducted to quantify the influence of specimen thickness and orientation on the mechanical properties of selective laser melted stainless steel 316 L. The results indicate that the mechanical strength and ductility increase with increasing specimen thickness until a saturation value is reached from a specimen thickness of about 2 mm. Specimen orientation dependency is pronounced for thin specimens (<1.5 mm), whereas only small deviations in strength are observed for thicker specimens with orientations of 30°, 45° and 90° to build direction. The mechanical properties of the specimen orientation of 0° to build direction shows great deviation to the other orientations and the smallest overall strength. A reliable design of selective laser melted components should account for specimen thickness and orientation, e. g. by a correction factor. Furthermore, it is recommended to avoid loads vertical (90°) and parallel (0°) to build direction to guarantee higher ductility and strength. Abstract : The influence of specimen thickness on the mechanical properties of selective laser melted 316 L is investigated for different specimen orientations. Mechanical strength and ductility increase with increasing specimen thickness until a saturation value is reached from a thickness of about 2 mm. For the design of filigree structures the structural size and orientation should be considered. Translation abstract: Anhand von experimentellen Untersuchungen wird der Einfluss der Probendicke und ‐orientierung auf die mechanischen Eigenschaften von selektiv lasergeschmolzenem Edelstahl 316 L ermittelt. Die Ergebnisse zeigen, dass die mechanische Festigkeit und Duktilität mit zunehmender Probendicke ansteigt bis ein Sättigungswert ab einer Probendicke von etwa 2 mm erreicht wird. Die Abhängigkeit der mechanischen Eigenschaften von der Probenorientierung ist bei dünnen Proben (<1.5 mm) stark ausgeprägt, während bei dickeren Proben mit Orientierungen von 30°, 45° und 90° zur Baurichtung nur geringe Abweichungen in der Festigkeit beobachtet werden. Die mechanischen Eigenschaften der Probenorientierung von 0° zur Baurichtung zeigt große Abweichungen zu den anderen Orientierungen, sowie die geringste Festigkeit. Eine zuverlässige Auslegung von selektiv lasergeschmolzenen Bauteilen sollte die Probendicke und ‐orientierung z. B. durch einen Korrekturfaktor berücksichtigen. Außerdem sollten Belastungen senkrecht (90°) und parallel (0°) zur Baurichtung vermieden werden, um eine höhere Duktilität und Festigkeit zu gewährleisten.